2015
DOI: 10.1111/joic.12216
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Early Invasive Approach on Outcomes of Patients With Acute Coronary Syndrome and Baseline Anemia: Analysis From the ACSIS Registry

Abstract: In the setting of ACS, despite the presence of baseline anemia, early coronary angiography with subsequent revascularization, when indicated, was associated with improved clinical outcomes including 1-year mortality without significant increase in rates of major bleeding.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
11
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 44 publications
3
11
0
1
Order By: Relevance
“…22 Studies which examine the impact of anemia on patients with ACS treated by primary PCI have found that anemia was a powerful marker of poor prognosis. 1,5,7,10,15,[22][23][24] Though one study suggests that early coronary angiography and PCI in an anemic STEMI cohort was associated with improved clinical outcomes and a comparable incidence of bleeding with the anemic cohort who did not undergo PCI. 15 A more recent retrospective study suggests that timely primary PCI in anemic STEMI patients had no increase in mortality but a penalty of major bleeding when compared to STEMI patients without anemia.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…22 Studies which examine the impact of anemia on patients with ACS treated by primary PCI have found that anemia was a powerful marker of poor prognosis. 1,5,7,10,15,[22][23][24] Though one study suggests that early coronary angiography and PCI in an anemic STEMI cohort was associated with improved clinical outcomes and a comparable incidence of bleeding with the anemic cohort who did not undergo PCI. 15 A more recent retrospective study suggests that timely primary PCI in anemic STEMI patients had no increase in mortality but a penalty of major bleeding when compared to STEMI patients without anemia.…”
Section: Discussionmentioning
confidence: 99%
“…1,5,7,10,15,[22][23][24] Though one study suggests that early coronary angiography and PCI in an anemic STEMI cohort was associated with improved clinical outcomes and a comparable incidence of bleeding with the anemic cohort who did not undergo PCI. 15 A more recent retrospective study suggests that timely primary PCI in anemic STEMI patients had no increase in mortality but a penalty of major bleeding when compared to STEMI patients without anemia. 24 There is general agreement that the management of ACS patients should incorporate anemia into the overall PCI strategy but there are no guidelines directly addressing this common clinical dilemma.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous reports have suggested that ACS patients with anaemia have significantly worse inhospital and longer-term total and cardiac mortality outcomes, heart failure, and risk of major bleeding and of reinfarction. [5][6][7][11][12][13][14][15] Some studies have reported that, once differences in age or comorbidity burden between anaemic/non-anaemic ACS cohorts are adjusted for, anaemia is no longer an independent predictor of adverse mortality or cardiovascular mortality, although other studies report that the relationship persists. 6,7,[15][16][17][18] Other studies have reported different relationships between anaemia and cardiovascular (CV) outcomes according to sex, with baseline anaemia independently associated with higher rates of all-cause and cardiac mortality at 30 days and 1 year in men but not in women.…”
mentioning
confidence: 99%